4
$\begingroup$

We begin by considering the limit: $$\lim_{\displaystyle x \to \frac{\pi}{2}}{\frac{\cos{x}}{\sin{x}-1}}$$ By applying L' Hôspital's rule to each side of the limit, we can prove that they are different and so the limit therefore does not exist. Furthermore, it can be proven like this: $$\lim_{\displaystyle x \to \frac{\pi}{2}}{\frac{\cos{x}}{\sin{x}-1}}=\lim_{\displaystyle x \to \frac{\pi}{2}}{\frac{\cos{x}(\sin{x}+1)}{-\cos^2{x}}}=\lim_{\displaystyle x \to \frac{\pi}{2}}{\frac{\sin{x}+1}{-\cos{x}}}$$ and now by checking each side of the limit, I have definitively concluded that the limit does not exist. However, I got curious and tried a $u$-substitution, by setting $u=\displaystyle x-\frac{\pi}{2}$ and then of course $u_0=\lim_{x \to \frac{\pi}{2}}{\left(\displaystyle x-\frac{\pi}{2}\right)}=0$ and so the limit becomes: $$\lim_{\displaystyle x \to \frac{\pi}{2}}{\frac{\cos{x}}{\sin{x}-1}}=\lim_{u \to 0}{\frac{\sin{x}}{-\cos{x}-1}}=0$$ What is the substitution not valid in the last method or why does it not work?

$\endgroup$
5
  • 1
    $\begingroup$ Do you mean, $$\lim_{\displaystyle x \to \frac{\pi}{2}}{\frac{\cos{x}}{\sin{x}-1}}=\lim_{u \to 0}{\frac{\sin{u}}{-\cos{u}-1}}=0$$, and if so, where did $\lim_{u \to 0}{\frac{\sin{u}}{-\cos{u}-1}}=0$ come from? $\endgroup$ Jan 29 at 15:21
  • $\begingroup$ You may also be interested in math.stackexchange.com/questions/1342202/… $\endgroup$
    – pre-kidney
    Jan 29 at 15:22
  • $\begingroup$ The last limit should be that for $\frac{\sin u}{\cos u-1}$ $\endgroup$
    – blamocur
    Jan 29 at 15:25
  • $\begingroup$ Nomenclature: L'Hôpital's rule, or L'Hospital's rule, but not L'Hôspital's rule. $\endgroup$ Jan 30 at 0:11
  • $\begingroup$ Not strictly relevant to your question, but please do not put \displaystyle in the bottom of \lim. That is really a pain to the eye. Write instead simply \lim_{x\to\pi/2} to get $$\lim_{x\to\pi/2}$$ which looks way better. $\endgroup$
    – YiFan
    Jan 30 at 12:23

1 Answer 1

7
$\begingroup$

Your substitution was incorrect. $$\lim_{ x \to \frac{\pi}{2}}{\frac{\cos{x}}{\sin{x}-1}}=\lim_{u \to 0}{\frac{\cos(\color{red}{u+\frac{\pi}2})}{\sin(\color{red}{u+\frac{\pi}2})-1}}=\lim_{u \to 0}{\frac{-\sin{u}}{\cos{u}-1}}$$

which yields the expected result

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.